Service Quality Improvement Strategy in Increasing Customer Satisfaction - Muhammad Farid Abrar; Rohid Akbar; Isnaini Harahap; Muhammad Yafiz (Proceeding International Conference on Islamic Economics Community Services (ICIECS), 2023)
This article discusses the effect of service quality on customer satisfaction at Warung Bakso Iga Sapi Evi Sugik, which has been operating since 2019 in Titi Besi, Batang Serangan District, Langkat Regency. With increasing competition in the culinary field, this research uses in-depth interviews and training methods to understand customer expectations and improve service quality. The results showed that customers and management have not fully realized the importance of service quality. The training provided aims to speed up serving time, increase employee responsiveness, and create a comfortable environment. The findings show that good service quality, including the dimensions of reliability, responsiveness, assurance, empathy, and physical evidence, significantly affects customer satisfaction. By implementing a strategy that focuses on improving quality and customer satisfaction, Warung Bakso Iga Sapi Evi Sugik is expected to strengthen competitiveness and increase sales.